Training loads in the starting period of sports dancers in Latin American style - Wojciech Kupczak; Elżbieta Szymańska; Jakub Kozłowski; Jan Baran; Katarzyna Chamera-Cyrek; Dawid Rowiński; Karolina Popielec; Anna Piotrowska (Journal of Kinesiology and Exercise Sciences)
Background: Undoubtedly, in all areas of physical culture, dance has an extremely positiveimpact on the formation of virtually all motor skills - conditioning, coordination, also affectsagility, speed and flexibility. The aim of this study was to evaluate the level of training loadsin a six-week mesocycle during the starting period of athletes of Latin American style sportballroom dancing and to study the effect of training loads on body fat and energyexpenditure.Methods: The study group consisted of 4 sport-active dance couples with about 12 years ofexperience. Sport-testers (POLAR H7) were used to evaluate training loads. training logsand a body composition analyzer. Results were compared between men and women.Results: The men's group showed higher values of the following training indicators: averagetraining time, energy expenditure, average heart rate. Statistically significant differencesbetween male and female dancers showed such factors as average energy expenditure,average percentage of work in the fifth zone of exercise intensity - in favor of men whileaverage percentage of fat burned - in favor of women.Conclusion: Based on the analysis of energy expenditure and with regard to theclassification of work severity, the dancers performed heavy and very heavy work during thecompetition period, and spent the vast majority of their preparation time in aerobic zones.Accordingly, coaches of Latin American dancers in their own work did not take into accountthe specific physiological workloads performed by them during dance competitions.